The value chain-based on competitiveness strategy for improvement strategy on prefab products - Elistioko, Dwi Nugraha Anton; Anggraeni, Elisa; Indrawan, Dikky (Indonesian Journal of Multidisciplinary Science, 2023)
Prefab building construction is chosen because the construction process is faster than conventional buildings, especially in emergency situations such as the COVID pandemic. The main problem at PT XYZ in selling prefabs is the price. The price components that affect the high price are COGS prefab, expedition cost, insurance cost and installation cost. This problem needs to be evaluated starting from production costs, supply chain to installation costs in order to provide a price quote that can be below the ceiling price of the buyer or owner, which is what the research attempted to discuss. Referring to these problems, in this research the authors used a descriptive method, a case study approach with data processing and analysis techniques consisting of descriptive analysis of the company and analysis of the company's internal and external environment. The analysis, which is used to formulate strategies and the process of using them, is Value Chain analysis, SAP-LAP Analysis, and Analytic Hierarchy Process (AHP). This analysis is interrelated in determining the weight on the Analytic Hierarchy Process (AHP), Hierarchy to determine Strategies to improve Competitiveness Based on Value Chain on Prefab Products. The highest weight value is Improving Product Quality with a weight value of 0.433. What is meant by improving product quality is meeting quality standards. This product quality improvement starts from the quality of the vendor's product materials, the production process in the factory, the handling process during the manufacturing process, and the quality of the product.